A test of galaxy cluster fundamental plane for the X-COP sample. Issue 1 (1st January 2022) - Pradyumna, S.; Desai, Shantanu
Abstract: We test the galaxy cluster fundamental plane using the X-COP sample of 12 clusters. The fundamental plane is given by the relation TX ∝ Ms α rs β, where TX, Ms, and rs correspond to the gas temperature, NFW halo mass, and scale radius, respectively. We did this analysis using two different temperatures: the error-weighted temperature in (50–500)h -1 kpc as well as the mass-weighted temperature in the same range. With both these temperatures, we find a very tight fundamental plane with dispersion of about 0.02 dex. The best-fit values for α and β are in-between those expected from virial equilibrium and self-similarity solution for secondary infall and collapse, with α being closer to the virial expectation. Our best-fit values are also consistent with a recent re-analyses of the fundamental plane for the CLASH sample, after excluding the hottest clusters.